PEDAGOGICAL FEATURES OF DEVELOPMENT OF PROFESSIAONAL COMPETENCE OF EXPERTS - Genrikh V. Yustus (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article focuses on the structure and content of the model of development of professional competencies of specialists with the help of training forms of learning. The article traces the main principles and stages of building the training systems of professional and personal competencies of staff of organizations. The main changes that may occur in the pedagogical activity were outlined. High quality of educational services may occurs if the coach will dynamically reacts and transforms his operations in accordance with the changes in the domestic and global educational and information space.